2020
DOI: 10.3390/jcm9051509
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy Using Talaporfin Sodium for Local Failure after Chemoradiotherapy or Radiotherapy for Esophageal Cancer: A Single Center Experience

Abstract: A phase II study of second-generation photodynamic therapy (PDT) using talaporfin sodium has shown excellent treatment results for esophageal cancer with local failure after chemoradiotherapy (CRT) or radiotherapy (RT). However, only a few studies have reported this therapy in clinical practice. This study aimed to confirm the efficacy and safety of salvage PDT using talaporfin sodium for esophageal cancer in various clinical situations. Twelve patients with esophageal cancer with local failure after definitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…68 Ishida et al reported an esophageal stricture rate of 41.7%. 68 Treatment-related death rates were 2.6% 59 and 1.8%. 67 Hatogai reported 5-year OS rates of 41.6% 59 and 36.9%, 67 and that cN status before dCRT was the only factor significantly associated with OS on multivariate analysis.…”
Section: Salvage Photodynamic Treatment (Pdt)mentioning
confidence: 97%
“…68 Ishida et al reported an esophageal stricture rate of 41.7%. 68 Treatment-related death rates were 2.6% 59 and 1.8%. 67 Hatogai reported 5-year OS rates of 41.6% 59 and 36.9%, 67 and that cN status before dCRT was the only factor significantly associated with OS on multivariate analysis.…”
Section: Salvage Photodynamic Treatment (Pdt)mentioning
confidence: 97%
“…Studies on PDT as salvage therapy for local failure following CRT on esophageal cancer have shown significant treatment improvements and survival outcomes. These studies reported complete response rates of 98.3% [18], 83.3% [19], and 58.4% [20]. Furthermore, the overall survival rates were 41.1% (5-year) and 80.0% (2-year) survival rates, respectively.…”
Section: Classic Treatment Of Esophageal Cancermentioning
confidence: 97%
“…Talaporfin sodium is an efficient curative and salvage therapy for esophageal cancer with local failure following chemoradiotherapy without metastases. It has no adverse effect and is shown to improve the overall survival rate and patient quality of life; however, it is suboptimal for more extensive tumors [18,19,49,55].…”
Section: Photosensitizer For Esophageal Cancer Pdt Applicationsmentioning
confidence: 99%
“…Minamide et al reported a retrospective comparative study between PDT u porfin sodium and porfimer sodium in patients with local failure after CRT [26]. complete response was better in patients treated with PDT using talaporfin sod pared with PDT using porfimer sodium (69.0% vs. 58.1%), although the differ After approval for clinical usage in Japan, PDT using talaporfin sodium followed by diode laser illumination for local failure after CRT or radiotherapy for esophageal cancer is gradually spreading, and there are several reports of the single-center experiences [24][25][26][27]. Minamide et al reported a retrospective comparative study between PDT using talaporfin sodium and porfimer sodium in patients with local failure after CRT [26].…”
Section: Clinical Practice Of Pdt Using Talaporfin Sodium For Esophageal Cancermentioning
confidence: 99%